Study of the effect of addition of extract, licorice root plant in the blood in some recipes Of chicken meat: Muhammed K. Al-maliki , Saffa A. Abed ,Ali A. Al-Yaseen - Al-maliki, Muhammed K. (The Iraqi Journal of Veterinary Medicine, 2009)
In study, the experiment design to know effect of addition of extract licorice root plant in the blood in some recipesOf chicken meat ,Used ((120) of the type of LOhemen chicks were divided randomly into four groups, the rate of(30) for each group and the experiment lasted 8 weeks and given feed and food transactions: the first group(control) was given free licorice root powder and the second group: was added (0.025%) Group III: were added(0.050%) and Group D: was added (0.075%) of powdered Licorice root plants as well as withThe summary of the study emphasizes that the best ratio of assists Licorice root powder added to, which have apositive impact on some of the characteristics of the blood of meat such as chicken red blood cells and the volumeof packed blood cells and hemoglobin resulting from the addition of licorice root powder by (0,050%) also have apositive impact on reducing the proportion of cholesterol in spite of the lack of impact on the white cells and thenot effective and its bad for the greater concentration of total protein and the proportion of cells to the lymphconcentration of glucose